ANALISIS INSTRUMEN ASSESMENT PEMBELAJARAN PAI BERBASIS MULTIKULTURAL - Chasanah, Uswatun; Yatmi, Yatmi; Hidayah, Ian Fii Barril; Purwoko, Purwoko (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
This study aims to analyze the Islamic Religious Education (PAI) learning assessment instrument based on multiculturalism in the educational environment in Indonesia. The diversity of cultures, ethnicities, and religions in Indonesia requires an inclusive learning approach that respects diversity, including in the PAI learning assessment process. This study uses a qualitative approach with literature study methods and document analysis. The results of the study indicate that the development of multicultural-based PAI assessment instruments needs to consider the principles of justice, inclusiveness, authenticity, comprehensiveness, and sustainability. Multicultural-based PAI learning assessment instruments need to cover various aspects of learning outcomes, namely cognitive, affective, and psychomotor aspects. The development of multicultural-based PAI assessment instruments involves a series of systematic stages, starting from needs and context analysis, formulation of assessment objectives, development of grids, instrument construction, review and validation, trials, to revision and finalization. The implementation of multicultural-based PAI assessment instruments in schools is influenced by various factors, including teacher competence, policy support, availability of resources and practical examples, as well as teacher perspectives and attitudes towards multicultural education. Evaluation of the impact of implementing multicultural-based PAI assessment instruments needs to be carried out systematically to determine their effectiveness and relevance in achieving inclusive and responsive PAI learning objectives towards diversity. The results of this study are expected to contribute to the development of PAI assessment instruments that are more inclusive and responsive to cultural diversity in Indonesia. ABSTRAKPenelitian ini bertujuan untuk menganalisis instrumen assessment pembelajaran Pendidikan Agama Islam (PAI) berbasis multikultural pada lingkungan pendidikan di Indonesia. Keberagaman budaya, etnis, dan agama di Indonesia membutuhkan pendekatan pembelajaran yang inklusif dan menghargai keberagaman, termasuk dalam proses assessment pembelajaran PAI. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi literatur dan analisis dokumen. Hasil penelitian menunjukkan bahwa pengembangan instrumen assessment PAI berbasis multikultural perlu memperhatikan prinsip keadilan, inklusivitas, autentisitas, komprehensivitas, dan berkesinambungan. Instrumen assessment pembelajaran PAI berbasis multikultural perlu mencakup berbagai aspek hasil belajar, yaitu aspek kognitif, afektif, dan psikomotorik. Pengembangan instrumen assessment PAI berbasis multikultural melibatkan serangkaian tahapan yang sistematis, mulai dari analisis kebutuhan dan konteks, perumusan tujuan assessment, pengembangan kisi-kisi, konstruksi instrumen, telaah dan validasi, uji coba, hingga revisi dan finalisasi. Implementasi instrumen assessment PAI berbasis multikultural di sekolah dipengaruhi oleh berbagai faktor, antara lain kompetensi guru, dukungan kebijakan, ketersediaan sumber daya dan contoh praktis, serta perspektif dan sikap guru terhadap pendidikan multikultural. Evaluasi dampak penerapan instrumen assessment PAI berbasis multikultural perlu dilakukan secara sistematis untuk mengetahui efektivitas dan relevansinya dalam mencapai tujuan pembelajaran PAI yang inklusif dan responsif terhadap keberagaman. Hasil penelitian ini diharapkan dapat memberikan kontribusi terhadap pengembangan instrumen assessment PAI yang lebih inklusif dan responsif terhadap keberagaman budaya di Indonesia.